Numerical and experimental analysis of superelastic SMA bending springs in rotor systems. Issue 4 (7th February 2022) - Senko, Richard; Silva, Antonio A.; Rodrigues, Marcelo C.; Lima, Antônio G. B.; dos Reis, Rômulo P. B.; Guedes, Clotildes A. L.
Abstract: The application of Shape Memory Alloys with superelastic behavior (SMA–SE) to reduce vibrations in rotor systems has been studied in recent years. However, the current SMA damper device design does not prioritize improving the distribution of applied force due to vibration levels. In this sense, this paper aims to study (theoretical and experimentally) two different types of passive damper devices made of a Ni-Ti SMA–SE to be incorporated in a rotor system in order to reduce mechanical vibrations. Two different physical situations were analyzed in two new designs (A and B) of SMA–SE bending springs. In order to obtain parameters similar to real conditions for the displacement and cycle routines of simulation, experimental tests were made with an unbalanced rotor system first, where the maximum displacement was used for simulations as extreme conditions for this kind of system. The first study was the application of loads and releases, the second is related to applications of preloads and peak-to-peak displacement variations with the aim of verifying real conditions. From the obtained results, it was verified that the damper design of device A reached a better performance (5.63% of specific damping capacity) than that of device B (2.65% of specific damping capacity) during the martensitic transformation, and reaching the full martensitic transformation with less displacement applied for the first setup. For the second setup, the device A reached 12.63% and device B reached 6.44% of the specific damping capacity. Thus, the bending springs of type A are more efficient in reducing mechanical vibration using the damping properties of the SMA-SE.